Assessment of Landslide Hazard in Jiangxi Using Geo-information Technology - Ou, Penghui; Wu, Weicheng; Qin, Yaozu; Zhou, Xiaoting; Huangfu, Wenchao; Zhang, Yang; Xie, Lifeng; Huang, Xiaolan; Fu, Xiao; Li, Jie; Jiang, Jingheng; Zhang, Ming; et al. (Frontiers in Earth Science, 2021)
Landslide constitutes a severe environmental problem in Jiangxi, China. This research was aimed at conducting landslide hazard assessment to provide technical support for disaster reduction and prevention action in the province. Fourteen geo-environmental factors, e.g., slope, elevation, road, river, fault, lithology, rainfall and land cover types, were selected for this study. A test was made in two cases: 1) only based on the main linear features, e.g., main rivers and roads, and 2) with detailed complete linear features including all levels of roads and rivers. After buffering of the linear features, an information value (IV) analysis was applied to quantify the distribution of the observed landslides for each subset of the 14 factors. The results were input into the binary logistic regression model (LRM) for landslide risk modeling taking the known landslide points as training set (70% of the total 9525 points). The calculated probability of landslide was further classified into five grades with an interval of 0.2 for hazard mapping: very high (3.70%), high (4.05%), moderate (18.72%), low (27.17%) and stable zones (46.36%). The accuracy was evaluated by AUC (the area under the ROC (Receiver Operator Characteristic) curve) versus the validation set (30%, the remained landslides). The final results show that with increasing the completeness of the linear features, the modeling reliability also significantly increased. We hence concluded that the tested methodology is capable of achieving the landslide hazard prediction at regional-scale and the results may provide technical support for geohazard reduction and prevention in the studied province.